Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(5+\frac{96}{x^2-16}=\frac{2x-1}{x+4}-\frac{3x-1}{4-x}\)
\(\frac{5\left(x^2-16\right)+96}{x^2-16}=\frac{\left(2x-1\right)\left(x-4\right)}{\left(x+4\right)\left(x-4\right)}+\frac{\left(3x-1\right)\left(x+4\right)}{\left(x-4\right)\left(x+4\right)}\)
\(\frac{5x^2-80+96}{x^2-16}=\frac{2x^2-9x+4+3x^2+11x-4}{x^2-16}\)
\(\Leftrightarrow5x^2+16=2x^2-9x+4+3x^2+11x-4\)
\(\Leftrightarrow5x^2-2x^2-3x^2+9x-11x+16-4+4=0\)
\(\Leftrightarrow-2x+16=0\)
\(\Leftrightarrow-2x=-16\)
\(\Leftrightarrow x=8\)
vậy \(x=8\)
\(\frac{x+1}{x-1}-\frac{x-1}{x+1}=\frac{16}{x^2-1}\)
\(\frac{\left(x+1\right)^2}{\left(x-1\right)\left(x+1\right)}-\frac{\left(x-1\right)^2}{\left(x-1\right)\left(x+1\right)}=\frac{16}{x^2-1}\)
\(\Rightarrow\left(x+1\right)^2-\left(x-1\right)^2=16\)
\(\Rightarrow\left(x+1-x+1\right)\left(x+1+x-1\right)=16\)
\(\Rightarrow2\left(2x\right)=16\)
\(\Rightarrow4x=16\)
\(\Rightarrow x=4\)
vậy \(x=4\)
\(\frac{6x+1}{x^2-7x+10}+\frac{5}{x-2}=\frac{3}{x-5}\)
\(\frac{6x+1}{\left(x-2\right)\left(x-5\right)}+\frac{5\left(x-5\right)}{\left(x-2\right)\left(x-5\right)}=\frac{3\left(x-2\right)}{\left(x-2\right)\left(x-5\right)}\)
\(\Rightarrow6x+1+5x-5=3x-6\)
\(\Rightarrow11x-3x=-6+4\)
\(\Rightarrow8x=-2\)
\(\Rightarrow x=\frac{-1}{4}\)
3) \(\frac{1}{x-1}+\frac{2x^2-5}{x^3-1}=\frac{4}{x^2+x+1}\)
\(\frac{x^2+x+1}{x^3-1}+\frac{\left(2x^2-5\right)}{x^3-1}=\frac{4\left(x-1\right)}{x^3-1}\)
\(\Rightarrow x^2+x+1+2x^2-5=4x-4\)
\(\Rightarrow3x^2-3x=-4+4\)
\(\Rightarrow3x\left(x-1\right)=0\)
\(\Rightarrow\orbr{\begin{cases}3x=0\\x-1=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=0\\x=1\end{cases}}\)
Bài 2:
\(A=x^2+2x+2012\)
\(=\left(x^2+2x+1\right)+2011\)
\(=\left(x+1\right)^2+2011\)
Ta có: \(\left(x+1\right)^2\ge0,\forall x\)
\(\Rightarrow\left(x+1\right)^2+2011\ge2011,\forall x\)
Hay \(A\ge2011,\forall x\)
Dấu "=" xảy ra \(\Leftrightarrow\left(x+1\right)^2=0\)
\(\Leftrightarrow x+1=0\)
\(\Leftrightarrow x=-1\)
Vậy Min A=2011 tại x=-1